An Option Valuation Analysis of Investment Choices by a Regulated Firm - Teisberg, Elizabeth Olmsted (Management Science, 1994)
This paper analyzes a utility power plant construction project using an option pricing model of the value of the capital investment. It includes descriptive factors frequently ignored in the valuation of capital investments by regulated firms, including lead time, lumpy and sequential cost outlays, irreversibility of expenditures, and uncertainty about regulatory outcomes for completed projects. The analysis shows the value of shorter lead time technologies, the value of flexibility to delay or abandon construction, the incentive to delay construction under uncertain regulation, and how cost recovery policies, such as possible disallowance of Allow for Funds Used During Construction (AFUDC), create incentives to invest less, but to complete construction quickly. The analysis may also apply in unregulated contexts, where the value of a completed project is affected by taxation, the possibility of nationalization, or possible competitors' actions that create uncertain restrictions on potential profits.